The minimum basic needs approach to development the Davao del Norte innovations - Del Rosario, Rodolfo P. (2002)
The adoption of the Minimum Basic Needs strategy to adequately and efficiently respond to the problems of poverty and underdevelopment has been the showcase program of the provincial government of Davao del Norte in order for development concerns to be immediately addressed. The quality of life of the people could be best improved if the basic needs for survival, security from harm and the enabling needs of the individual, family and community are met and prioritized. The article illustrates that there is a need to reinvent service delivery initiatives to make them responsive to the people's basic needs. By identifying the needs of the people, prioritizing projects and focusing attention on target beneficiaries, the provincial government is able to effectively deliver basic services while efficiently managing meager resources.
Keywords: Minimum Basic Needs (MBN) Approach -- Davao del Norte; People's participation -- Davao del Norte; Service delivery initiatives -- Davao del Norte